On the passivation mechanism of poly-silicon and thin silicon oxide on crystal silicon wafers. (December 2019) - Rui, Zhe; Zeng, Yuheng; Guo, Xueqi; Yang, Qing; Wang, Zhixue; Shou, Chunhui; Ding, Waner; Yang, Jie; Zhang, Xinyu; Wang, Qi; Jin, Hao; Liao, Mingdun; et al.
Graphical abstract: Highlights: The passivation mechanism of poly-Si/SiOx on c-Si wafer is systematically studied. The chemical passivation by an undoped poly-Si occurs only after a proper hydrogenation. The chemical passivation improves the iVoc to 733 mV, J0 to 2.45 fA/cm 2, and τeff to 2.8 ms. The field effect by n + -poly-Si/SiOx improves the passivation quality further. An outstanding passivation quality of iVoc  = 747 mV, J0  = 1.34 fA/cm 2, and τeff  = 8.4 ms is achieved. The p + -poly-Si/SiOx is much poorer than n + -ploy-Si/SiOx, caused by the BO defect formation. Abstract: A systematic study on the passivation quality using various poly-Si/SiOx bi-layers on c-Si is carried. We find that no any passivation effect is observed with undoped a-Si:H/SiOx and as-crystallized poly-Si/SiOx, a hydrogenation improves the passivation noticeably to reach i V oc of 733 mV. These observations imply that the chemical passivation by the undoped poly-Si/SiOx occurs only after the effective hydrogenation. The passivation with doped poly-Si/SiOx layers shows different behaviors. The n + -poly-Si already shows a reasonable good passivation with i V oc of 715 mV and 685 mV on the n-type and p-type wafers, respectively, after the crystallization without hydrogenation, and the hydrogenation improves the i V oc to 747 mV and 736 mV. The p + -poly-Si shows a poorer passivation quality than both the undoped poly-Si and n + -poly-Si, with the i V oc of 690 mV and 640 mV on the n-type and p-type c-Si wafers after the crystallization, respectively, and 707 mV and 670 mV after the hydrogenation. It concludes that the field passivation appears immediately after the crystallization, and an effective hydrogenation improves the passivation quality further. The passivation quality with the p + -poly-Si is poorer than the n + -poly-Si, which is speculatively caused by the higher interface recombination in the SiOx /c-Si region because of the higher capture cross section for electrons than holes and by additional Shockley-Read-Hall recombination through BO complex defects.